Hand layup: understanding the manual process. (24th October 2015) - Elkington, M.; Bloom, D.; Ward, C.; Chatzimichali, A.; Potter, K.
Graphical Abstract: Abstract : The hand layup of pre-impregnated woven materials is still a large part of the composite manufacturing industry, requiring the skills and experience of a human workforce to form flat plies into complex shapes. It is capable of producing high performance and complex parts, but can be an expensive and variable process. Despite its importance, there appears to have been very little research into the actual methods and techniques used by workers to manipulate flat sheets of composite material into shape during layup. This work presents the first known detailed study of the approach and techniques used by laminators. Four participants laid up onto 15 different shaped molds that replicated features commonly found on composite components. The actions used in layup were grouped into eight distinct techniques. Use of these techniques across tasks of different geometry, ramp angles, radii and drape path was identified using video analysis techniques from the ergonomics field. This revealed strong links between specific features and techniques, revealing a systematic approach to layup. This has enabled the first step toward producing a design for manufacture knowledge base surrounding hand layup. This could then be used to inform the development of the layup process, improve training methods and assist in the design of future automated solutions.